Circulating tumor cells with epithelial-mesenchymal transition markers as potential biomarkers for the diagnosis of lung cancer - Jiang, Sha-Sha (World J Clin Cases, 2021)
BACKGROUND: Circulating tumor cells (CTCs) can be clustered into three subtypes according to epithelial-mesenchymal transition (EMT) markers: CTCs with epithelial markers (E-CTCs), CTCs with mesenchymal markers (M-CTCs), and CTCs with both markers (E&M-CTCs). CTC detection has clinical implications in the diagnosis of lung cancer (LC). AIM: To clarify the diagnostic value of CTCs categorized by EMT markers in LC. METHODS: The study included 106 patients with lung adenocarcinoma, including 42 ground-glass opacities (GGO) and 64 solid lesions, who underwent surgery between July 2015 and December 2019. Eleven patients with benign tumors and seventeen healthy controls were included. CTCs in peripheral blood and associated EMT markers were detected preoperatively using the CanPatrol(TM) technique. The diagnostic power of CTCs for discriminating LC cases from controls was analyzed by the receiver operating characteristic (ROC) curve. The CytoploRare technique was used in 20 cases and 18 controls for validation, and Kappa values were calculated to evaluate consistency between techniques. RESULTS: Of the 106 LC cases, 94 (89.6%) had at least one CTC. CTCs were detectable in 35 (83.3%) of 42 GGO cases. Total CTCs and E&M-CTCs were significantly more frequent in LC cases than in benign or healthy controls. The proportion of M-CTCs plus E&M-CTCs increased gradually from healthy controls, to benign controls, to LC cases. The area under the ROC curve of total CTCs and E&M-CTCs was > 0.8 and > 10.75, respectively. The combined sensitivity of total-CTCs and E&M-CTCs was 85.85% for LC patients (80.95% for GGO patients) and the specificity was 78.57%. The Kappa value was 0.415, indicating relative consistency between CanPatrol(TM) and CytoploRare. CONCLUSION: CTC detection is valuable for distinguishing LC from controls, and particularly E&M-CTC detection warrants further study.